A Course of Mathematical Analysis - Volume 2 - Nikolsky, S.M (Mir, 1975)
This book for university students(physicists and mathenaticians) with special supplementary material an mathermatical physics. Based on the course read by the author at the Moscow Physico-Technical Institute. Volume 2 contains multiple intergrals, field theory, Fourier series and Fourier integral, diffential manifolds and differential forms, and the Lebesgue integral.